High-Speed Computer Simulation of Electrical Circuits - Volodymyr Moroz; Galina Sivyakova (Energy Engineering and Control Systems)
The well-known numerical-analytic method based on zeroes/poles matching (as z-transform realization) of equivalent transfer function or complex impedance (conductivity) in Laplace domain was proposed for high-speed computer analysis of electric circuits’ transients. The advantages of this method were illustrated on simple examples of the computer models of the first order electric circuit (RC-circuit that correspond to real pole) and second order electric circuit (RLC-circuit that correspond to complex pair of poles). These models were verified to the computer models based on the analytic method using the Laplace transform. The method can be applied to modern computer programs of power systems stability analysis, electrical circuits' transients' calculations and common systems dynamic analysis.